Effect of bidirectional fiber incorporation on tensile properties and drilling parameter optimization of cellulose bio fibers and glass fiber thermoset composites - R. Meenakshi Reddy; A. Thanikasalam; V. Mohanavel; P․C Santhosh Kumar; V. Chanakya Varma; Sathish Kannan; K. Selvakumar; Ram Subbiah; Manzoore Elahi M. Soudagar (Results in Engineering)
Plastics and composite materials have emerged as the main materials to use in the production of economically viable composite components during the past thirty years. The penetration of these modern materials has steadily increased in volume and usage, made possible by the reinforcing of more recent green natural fibers with polymer resin matrix materials. Thus, the focus of this study is on the impact of combining bidirectional Areca, Glass, and Pineapple Leaf (PALF) fibers with epoxy matrix. An analysis was conducted on the tensile characteristics and the drilling characterization. The fiber composition was determined to be the parameter that had the biggest impact on the quality of the drilled hole for natural fiber-reinforced composites using the Taguchi experimental design, which was employed in this work to optimize the process parameters. The composites produced in this study shown good agreement with the previous natural fiber reinforced polymer composites in terms of their tensile properties. The findings demonstrated the potential application of the composites described in this research to automotive interior and exterior components, including dashboards, engine bonnets, door panels, roof covers, and pumps, among others. These advantages include reduced weight, improved mechanical qualities, enhanced thermal stability, and good compatibility between fiber and matrix.